Renormalization constant for the local times of self-intersections of a diffusion process in the plane - Izyumtseva, O. L. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We study the local times of self-intersection of a diffusion process in the plane. Our main result is connected with the investigation of the asymptotic behavior of the renormalization constant of this local time.